Pengaruh Pemberian Video Animasi Mengenai Prosedur Operasional Alat Automatic External Defibrillator (AED) Terhadap Tingkat Pengetahuan Mahasiswa Keperawatan Poltekkes Kemenkes Pangkalpinang - Ginanjar, Sammy Lazuardi; Aini, Septy Nur; Juliani, Nekka (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
Cases of sudden cardiac arrest can occur anywhere and anytime beyond the hospital. The American Heart Association advocates using Automatic External Defibrillators as a tool to help the sudden cardiac arrest survivor. However, the previous study showed health workers have less knowledge of tool utilization. The study aimed to determine the influence of animated videos regarding the operational procedures on the level of knowledge of the Polytechnic Pangkalpinang Ministry of Health nursing students. The queasy experimental was used with a non-equivalent control group pre-test and post-test design approach. The total of 140 participants divided into intervention groups received animated videos while the control groups received guide book only. The questionnaires used have a validity value of each question item 0.05 and reliability showed by Cronbach alpha value of 0.732. Data were analyzed using Wilcoxon Test and The Mann-Whitney test to see the comparison between the groups. The results showed an increase in the average knowledge before and after being given the intervention. However, there was no significant effect of providing animated video on the level of knowledge of nursing students (p=0.055 ≥ 0.05), and there was no significant difference between groups (p=0.889 ≥ 0.05). The development of an easy-to-access application and various learning media for introducing other medical devices is recommended for further studies.